2020
DOI: 10.1111/adb.12890
|View full text |Cite
|
Sign up to set email alerts
|

Differential correlation of serum BDNF and microRNA content in rats with rapid or late onset of heavy alcohol use

Abstract: Heavy alcohol use reduces the levels of the brain‐derived neurotrophic factor (BDNF) in the prefrontal cortex of rodents through the upregulation of microRNAs (miRs) targeting BDNF mRNA. In humans, an inverse correlation exists between circulating blood levels of BDNF and the severity of psychiatric disorders including alcohol abuse. Here, we set out to determine whether a history of heavy alcohol use produces comparable alterations in the blood of rats. We used an intermittent access to 20% alcohol using the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 87 publications
0
14
0
Order By: Relevance
“…Hsa-miR-151a-3p was implicated in SSRI responsiveness and possibly in the clinical response to antidepressant drugs via down-regulating CHL1 expression (Oved et al, 2017). Hsa-miR-195-5p was increasingly expressed and targeted BDNF in rats with the rapid onset of heavy alcohol use (Ehinger et al, 2021). The altered expression of these DE-miRNAs was also found in individuals with other comorbid psychiatric disorders sharing genetic overlap with autism, including major depressive disorder, attention-deficit/hyperactivity disorder, and Alzheimer's disease (Mendes-Silva et al, 2016;Sánchez-Mora et al, 2019;Zadehbagheri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Hsa-miR-151a-3p was implicated in SSRI responsiveness and possibly in the clinical response to antidepressant drugs via down-regulating CHL1 expression (Oved et al, 2017). Hsa-miR-195-5p was increasingly expressed and targeted BDNF in rats with the rapid onset of heavy alcohol use (Ehinger et al, 2021). The altered expression of these DE-miRNAs was also found in individuals with other comorbid psychiatric disorders sharing genetic overlap with autism, including major depressive disorder, attention-deficit/hyperactivity disorder, and Alzheimer's disease (Mendes-Silva et al, 2016;Sánchez-Mora et al, 2019;Zadehbagheri et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Ehinger et al indicated an inverse correlation between blood serum BDNF levels and alcohol intake in rapid-onset and late-onset AUD rats. In contrast, the expression of miR-30a-5p, miR-195-5p, miR-191-5p and miR-206-3p, which were known to target BDNF, were robustly elevated in the serum of rapid-onset AUD rats [86]. It was found that the expression of miR-206 was significantly up-regulated in medial prefrontal cortex (mPFC) of rats with a history of AUD.…”
Section: The Mirnas Expression and Their-related Mechanisms In Aud An...mentioning
confidence: 98%
“…The expression of striatal BDNF correlates with the expression of CREB, TrkB, and pri-miR-132 following amphetamine application in rats [ 236 ]. Heavy alcohol use causes upregulation of some miRNAs and consequently regulates BDNF values [ 237 ]. Adolescent intermittent ethanol exposure increased the miR-137 expression level in the amygdala.…”
Section: The Role Of Nts-mirna Interaction In Neuropsychological Diso...mentioning
confidence: 99%